2022
DOI: 10.3389/fpain.2022.855493
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based EEG Neurofeedback Intervention for the Management of Chronic Pain

Abstract: BackgroundChronic pain and associated symptoms often cause significant disability and reduced quality of life (QoL). Neurofeedback (NFB) as part of a Brain Computer Interface can help some patients manage chronic pain by normalising maladaptive brain activity measured with electroencephalography (EEG).ObjectivesThis study was designed to assess the efficacy and safety of a novel home-based NFB device for managing chronic pain by modifying specific EEG activity.MethodsA prospective, single-arm, proof-of-concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Our results were encouraging and suggested that the BCI-based attention training program could be delivered via tablet at the patient’s own home without on-site therapist support. Although there is a dearth of research in home-based BCI interventions for ADHD, our findings are consistent with results from other independent home-based EEG neurofeedback interventions targeting chronic pain in adults [ 36 ], recovery of motor control after stroke [ 37 ] and social competence for college students with autism spectrum disorder (ASD) [ 38 ]. However, it should be noted that these studies are not directly comparable to our own given the difference in study population.…”
Section: Discussionsupporting
confidence: 87%
“…Our results were encouraging and suggested that the BCI-based attention training program could be delivered via tablet at the patient’s own home without on-site therapist support. Although there is a dearth of research in home-based BCI interventions for ADHD, our findings are consistent with results from other independent home-based EEG neurofeedback interventions targeting chronic pain in adults [ 36 ], recovery of motor control after stroke [ 37 ] and social competence for college students with autism spectrum disorder (ASD) [ 38 ]. However, it should be noted that these studies are not directly comparable to our own given the difference in study population.…”
Section: Discussionsupporting
confidence: 87%
“…3). The current selection of studies used heart rate sensors (n = 6) and respiratory sensors (n = 5), with 1 study using a wearable electroencephalogram (EEG) 8 and 1 study using a commercial smart bracelet to detect electrodermal activity. 52…”
Section: Resultsmentioning
confidence: 99%
“…This specific use case allows control of some crucial aspects of the EEG recording session (ie, participant static in a room with constant lighting and following precise instructions on a computer screen). However, only 1 study 8 discussed EEG data in relation to psychological or social variables, and in this case, theta (4–8 Hz), alpha (8-13 Hz), beta (13-30 Hz), and hi-beta (20-30 Hz) frequency bands were used for biofeedback. Decreased activity in relative hi-beta was associated with decreased anxiety and depression levels.…”
Section: Resultsmentioning
confidence: 99%
“…The home-based NFT led to improvements in sleep quality ( Krepel et al, 2022 ). Birch et al (2022) trained their participants remotely via a video link before the beginning of the NFT until they were able to mount the EEG headset, minimize EEG artifacts, and complete a full training session on their own. The home-based NFT sessions were performed without assistance from a supervising NF expert.…”
Section: Introductionmentioning
confidence: 99%
“…The home-based NFT sessions were performed without assistance from a supervising NF expert. Home-based NFT resulted in a significant pain reduction in patients with chronic pain ( Birch et al, 2022 ). The results of these studies provide evidence for the successful regulation of one’s own brain activity through home-based NFT.…”
Section: Introductionmentioning
confidence: 99%